FORECASTING THE NUMBER OF PASSENGERS FOR THE MEDAN-KUALANAMU TRAIN WITH TIME INVARIANT FUZZY TIME SERIES METHOD - Nasution, Pauziah; Huda Prasetya, Nurul; Rakhmawati, Fibri (Journal of Mathematics and Scientific Computing With Applications, 2022)
For forecasting, a forecasting model is needed. Forecasting to find out the increase or even decrease for the departure of Medan - Kualanamu for the next few years. Then the value generated by fuzzy logic is not yes, which has a value of 1, and is not worth 0. Time series is data that is collected from time to time, to describe the development of an activity. From the case of forecasting the number of passengers of the Medan-Kualanamu Train, the author will use the Time Invariant Fuzzy Time Series method. Based on the research, it is obtained that the forecasting of the number of passengers of the Medan-Kualanamu / Kualanamu-Medan train in 2021 is 182,874.9; and 2022 is 266,527,510.6 with AFER is 2,5%.